2020
DOI: 10.1186/s12879-020-05312-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial epidemiology and risk factors for relapse in gram-negative bacteria catheter-related bloodstream infection with a pilot prospective study in patients with catheter removal receiving short-duration of antibiotic therapy

Abstract: Background: Infectious Diseases Society of America (IDSA) guidelines suggest 7-14 days' duration of antibiotic treatment for uncomplicated Gram-negative bacteria (GNB) catheter-related bloodstream infection (CRBSI). The objectives of this study were to review microbial epidemiology, to determine rate and risk factors for relapse, and to compare clinical outcomes in patients receiving long-versus short-duration antibiotic therapy. Methods: A retrospective phase 1 study was conducted between January 2010 and Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…In comparison to ndings in previous studies, one of the new independent associated factors identi ed in this study was CLABSI/PLABSI. This result could be explained by the fact that P. aeruginosa is the most common gram-negative rod causing CLABSI/PLABSI, while E. coli is relatively rare [23,24]. A previous study showed the above trend, but the nding was not statistically signi cant [11].…”
Section: Discussionmentioning
confidence: 90%
“…In comparison to ndings in previous studies, one of the new independent associated factors identi ed in this study was CLABSI/PLABSI. This result could be explained by the fact that P. aeruginosa is the most common gram-negative rod causing CLABSI/PLABSI, while E. coli is relatively rare [23,24]. A previous study showed the above trend, but the nding was not statistically signi cant [11].…”
Section: Discussionmentioning
confidence: 90%
“…“phase 2”). The cases in the phase 2 were matched with controls of phase 1 and we only included the results of the case-cohort phase [ 29 ]. The total number of included patients was 780 with numbers ranging from 44 to 188 patients per study.…”
Section: Resultsmentioning
confidence: 99%
“…All cohort studies assessed the whole database of their institutions to identify patients fulfilling the inclusion criteria. Adult patients were included in four studies [ 24 , 26 , 27 , 29 ], whereas four studies included patients of all ages [ 22 , 23 , 25 , 28 ]. Catheter removal was mandatory for inclusion in five studies [ 22 24 , 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations